Update on Asthma Genetics: Results From Meta-Analyses of Candidate Gene Association Studies - Tizaoui, K.; Hamzaoui, K.; Hamzaoui, A. (Current Molecular Medicine, 2017)
Several studies have investigated the risk factors associated with asthma. Both genetic and environmental factors are considered to contribute to asthma susceptibility. Individual genetic association studies usually suffer from small sample size leading to biased results. Meta-analysis is a powerful tool that has the potential to resolve this limitation by increasing the statistical power of analyses. The current review summarizes the recent knowledge concerning genetic factors involved in asthma predisposition based on meta-analyses. Using the keywords: asthma, meta-analysis, polymorphism, we searched Pubmed, Medline, Embase and Google Scholar databases for the associated articles. Genetic polymorphisms in twenty-three genes are associated with asthma risk in meta-analyses. However, polymorphisms in nine genes showed none significant association. These findings are used to assess the genetic risk factors and to understand the molecular pathways related to asthma.
Keywords: Asthma